Stress Analysis of Load Cell Adaptor Designs For The Caliber450mm Solid Rocket Motor Static Test - Moranova, Starida; Putro, Idris Eko; Abrizal, Haryadi; Mariani, Lilis; Prianto, Bayu; Hanif, Azizul; Andiarti, Rika; Ekadj, Firza Fadlan (BRIN Publishing, 2023)
This study presents a structural analysis of two load cell adaptor designs for a caliber-450 mm solid rocket motor. The structural analysis of a C-shape load cell adaptor and the newly designed truncated-cone shape is presented incorporates a 30-degree truncated disc section and varies the thickness to 30 mm, 25 mm, and 20 mm. The numerical simulation using PATRAN reveals that by altering the arm thickness while maintaining the constant hinge thickness, the 30 mm thickness in the disc section yields the best local maximum stress. However, considering the global maximum stress, the 25 mm thickness emerges as the optimal design. The simulation results show that the 25 mm disc section of the load cell adaptor surpasses the aerospace standard safety factor (SF = 1.5) for both local and global maximum stress.